Design and optimization of the RF input-coupler for a low-frequency, split-coaxial RFQ. (26th August 2021) - Sangroula, M.P.; Winklehner, D.; Schuett, M.
Abstract: The Isotope Decay-At-Rest experiment (IsoDAR) is a proposed underground experiment which is expected to be a definitive search for sterile neutrinos. In order to be decisive within 5 years, high rates of neutrinos must be produced, by impinging a 10 mA continuous wave proton beam at 60 MeV on a high power target. Due to space restrictions, a compact cyclotron was chosen as an accelerator to produce this driver beam. To overcome space charge limitations during injection, H2 + ions are accelerated and later stripped into protons by means of a carbon foil. IsoDAR uses an especially designed low-frequency (32.8 MHz) split-coaxial Radio-Frequency Quadrupole (RFQ) to effectively bunch H2 + ions before injecting them into this cyclotron. The RFQ will be embedded vertically in the cyclotron yoke, facilitating a very compact design. This puts stringent limits on RFQ size, type, and accessibility. Here, we present the design and optimization of the low-frequency (32.8 MHz) RF input-coupler for the IsoDAR RFQ. The design is challenging due to the necessarily small diameter of the RFQ (28 cm) and the split-coaxial type, as well as limited access to the RFQ. We have determined the optimal position and shape for the coupler, leading to a low power consumption of < 6 kW for an inter-vane voltage of 22 kV. The highest calculated fields are safely below the Kilpatrick limit for this structure.